402 Which stress-related factors affect the mental health of nuclear emergency workers over a long period?. (24th April 2018) - Hiro, H; Hino, A; Mafune, K; Inoue, A; Shigemura, J; Yamada, M; Okubo, T
Abstract : Introduction: Fukushima Daiichi Nuclear Power Plant suffered serious damage the Great East Japan Earthquake and Tsunami of 2011. This study examines the association between mental health status and stress-related factors in the nuclear emergency workers 4–5 years after the disaster. Methods: In total, 1572 workers completed a self-administered questionnaire by mail. Mental health status was measured by the K6. The stress-related factors we evaluated life events, stress coping, sense of coherence, self-esteem, self-efficacy, resilience, social support, life satisfaction, job satisfaction and slanderous defamation. Multiple regression analysis was performed with the K6 score as the explained valuable and stress-related factors as the explanation valuables. Result: The K6 score was significantly high in the workers who had worked for a long period of time. It was also related to the scores of life events, stress coping, self-esteem, life satisfaction, work satisfaction and slanderous defamation. The slanderous defamation score most strongly related to the K6 score. Discussion: Long term follow-up is for nuclear emergency workers who work for long period of time, and slanderous defamation is one of the most important measures support the mental health of these workers